2019
DOI: 10.1093/tas/txz132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of holes in plastic film on the storage losses in total mixed ration silage in round bales

Abstract: The ensilage of total mixed ration (TMR) is a technology designed to help farmers with limitations to provide a balanced diet for their herds. Our aim was to evaluate the conservation of TMR ensiled in round bales with or without holes in the wrapping plastic film. Eight round bales of a corn silage-based TMR of 1,000 kg (370 kg DM/m3) were prepared. Ten days (d) after ensiling, four bales were randomly punctured with two holes of 25 cm2 each in opposite sides of the bale. The temperature in the center of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Of course, the final profile of fermentation products will depend on ration ingredients, DM content, storage length, and the temperature and application of additives [16,22,23]. Not rarely, TMR silages present high concentrations of lactic acid (e.g., >80 g.kg −1 DM) [6,8,[23][24][25]. Although this finding is seldomly discussed, the inclusion of urea, mineral mixtures, limestone, and buffers (e.g., sodium bicarbonate) certainly increases the buffering capacity and stimulates the formation of lactic acid in TMR silages, as previously reported for corn and sugarcane silages treated with alkaline substances [26][27][28].…”
Section: Soluble Carbohydrates and Fermentation End-productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, the final profile of fermentation products will depend on ration ingredients, DM content, storage length, and the temperature and application of additives [16,22,23]. Not rarely, TMR silages present high concentrations of lactic acid (e.g., >80 g.kg −1 DM) [6,8,[23][24][25]. Although this finding is seldomly discussed, the inclusion of urea, mineral mixtures, limestone, and buffers (e.g., sodium bicarbonate) certainly increases the buffering capacity and stimulates the formation of lactic acid in TMR silages, as previously reported for corn and sugarcane silages treated with alkaline substances [26][27][28].…”
Section: Soluble Carbohydrates and Fermentation End-productsmentioning
confidence: 99%
“…In the industry, TMR ingredients are usually mixed in stationary mixer wagons and stored in big bags (e.g., 300 to 400 kg) [7] or baled by agricultural compactors [8]. The latter are baler-wrapper combined machines (e.g., Orkel AS, Norway) able to pack the ingredients by tying the bale with plastic film and then wrapping the bale with stretch plastic film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total mixed ration (TMR) can be defined as a complete dietary source that includes forage, cereal grains, protein sources, by-products, minerals, vitamins, and additives, which meets the daily nutritional needs of livestock where they are kept indoors year round [ 1 ]. Today, the uniformly distributed balanced nutritional characteristics of TMRs make them popular worldwide due to their beneficial effect on ruminant nutrition, management, and production of ruminants [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mapping the surface temperature of the silo or feed bunker allows feeding management to minimize feed loss. Although some research has been carried out to monitor temperature differences during air exposure using the IRT method, no studies have been found that directly focus on the correlation between nutritional composition and the IRT values, and factors affecting these values [ 1 , 15 , 16 ]. Hence, this study aims at addressing these knowledge gaps in the state of the art by using principal components and multifactor analysis.…”
Section: Introductionmentioning
confidence: 99%